2011
DOI: 10.1111/j.1755-3768.2011.02185.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatment for 1 week with latanoprost but not diclofenac reduces the diameter of dilated retinal arterioles in patients with type 1 diabetes mellitus and mild retinopathy

Abstract: ABSTRACT.Purpose: Diabetic retinopathy is characterised by morphological lesions secondary to retinal vascular impairment, and it is assumed that changes in the diameter regulation of retinal arterioles are involved in the disease pathogenesis. It has previously been shown that prostaglandin F2a can constrict retinal arterioles in vitro. In the present study, we investigated whether a similar effect could be achieved by topical administration in diabetic patients with dilated retinal arterioles and retinopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
(31 reference statements)
5
23
0
Order By: Relevance
“…A recent in vitro study has shown that hypoxia-induced vasodilation depends on inducible NO in the perivascular retina [25], and supports the existence of an interaction between these two signaling pathways in vivo. The diameter responses during simultaneous flicker stimulation and isometric exercise were similar to those observed during flicker stimulation alone, which confirmed that metabolic autoregulation can overrule pressure autoregulation in order to adapt the blood flow to changes in retinal metabolism [28,30]. …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A recent in vitro study has shown that hypoxia-induced vasodilation depends on inducible NO in the perivascular retina [25], and supports the existence of an interaction between these two signaling pathways in vivo. The diameter responses during simultaneous flicker stimulation and isometric exercise were similar to those observed during flicker stimulation alone, which confirmed that metabolic autoregulation can overrule pressure autoregulation in order to adapt the blood flow to changes in retinal metabolism [28,30]. …”
Section: Discussionsupporting
confidence: 53%
“…The flicker-induced vasodilatation in the studied diabetic patients without retinopathy was reduced similarly to observations from diabetic patients [26,27,28,29,30], and during hypoxia the response was reduced further than in normal persons subjected to similar experimental conditions as in the present study [11]. L -NMMA has previously been found to increase flicker-induced dilatation of retinal vessels in normal persons [10] but had no significant effect in the studied diabetic patients without retinopathy.…”
Section: Discussionmentioning
confidence: 49%
“…The lack of contraction of retinal arterioles during isometric exercise explains why diclofenac was unable to affect this contraction during hypoxia, as has been shown previously in normal persons and in diabetic patients with minimal retinopathy during normoxia [31,38], and therefore the modulating effects of COX inhibition on retinal blood flow can be assumed to be less relevant in patients with diabetic maculopathy.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, retinal attenuation further increased with the progression of diabetic retinopathy (Mandecka et al. 2007; Tilma & Bek 2012). Retinal vascular dysfunction is proposed to contribute to the pathogenesis of diabetic retinopathy (Schmetterer & Wolzt 1999), but the exact microvascular changes that precede diabetes are not clearly understood (Caballero 2005).…”
Section: Discussionmentioning
confidence: 99%